Intraoperative cricothyroid muscle electromyography may contribute to the monitorization of the external branch of the superior laryngeal nerve during thyroidectomy - Aygun, Nurcihan; Unlu, Mehmet Taner; Kostek, Mehmet; Caliskan, Ozan; Isgor, Adnan; Uludag, Mehmet (Frontiers in Endocrinology, 2023)
Background: In thyroid surgery, both the recurrent laryngeal nerve (RLN) and external branch of the superior laryngeal nerve (EBSLN) should be preserved for maintaining the vocal cord functions. We aimed to evaluate whether EMG of the CTM applied after the superior pole dissection provided additional informative data to the IONM via ETT or not, regarding the EBSLN function. Methods: The prospectively collected data of the patients, who have undergone thyroidectomy with the use of IONM for the exploration of both the RLN and EBSLN between October 2016 and March 2017, were evaluated retrospectively. Patients over 18 years of age with primary thyroid surgery for malignant or benign thyroid disease, and whom were applied CTM EMG with a needle electrode after the completion of thyroidectomy were included in the study. In the study, each neck side was evaluated as a separate entity considering the EBSLN at risk. Results: The data of 41 patients (32 female, 9 male) (mean age, 46.7+9.1; range, 22-71) were evaluated. Sixty seven EBSLNs out of 26 bilateral and 15 unilateral interventions were evaluated. With EBSLN stimulation after the superior pole dissection, positive glottic EMG waveforms via ETT were obtained in 45 (67.2 %) out of 67, and the mean glottic amplitude value was 261+191 μV (min‐max: 116‐1086 μV). Positive EMG responses via the CTM EMG were achieved from all of the 67 EBSLNs (100%) with stimulation using a monopolar probe at the most cranial portion above the area of divided superior pole vessels. The mean value of CTM amplitudes via CTM EMG obtained with EBSLN stimulation was 5268 + 3916 μV (min‐max:1215 ‐19726 μV). With EBSLN stimulation, the mean CTM EMG amplitude was detected significantly higher than the mean vocal cord amplitude (p<0.0001). The CTM EMG provided more objective quantifiable data regarding the EBSLN function (100 % vs 67,2 %, p<0.001). Conclusion: In addition to the IONM via ETT, intraoperative post-dissection CTM EMG via needle electrode is a safe, simple and applicable method that may provide significant additional informative data to IONM with ETT by obtaining and recording objective quantitative data related to the EBSLN function.